A STUDY IN SCHOOL MANAGEMENT OF SCHOOL ADMINISTRATION’S SATISFACTION AT LOPBURI PRIMARY EDUCATIONAL SERVICE AREAS OFFICE 1 ACCORDNG TO THE THREEFOLD TRAINING - Phochuai , Kamonporn; Tongmun , Winai; Methiworachat , Anon (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aimed 1) to study the satisfaction of school administrators in Lopburi Primary Educational Service Area 1 based on the Tri-sikkh principle, and 2) to compare the satisfaction of school administrators in Lopburi Primary Educational Service Area 1 classified by individuals. This research was a quantitative research. Data were collected from a sample of 322 teachers, educational personnel and school committees. The research instrument was a scale and rating questionnaire with a reliability coefficient of 0.87 for the entire questionnaire. Data were analyzed by using frequency, percentage, mean, and standard deviation, t-test for independent samples, and one-way analysis of variance. The results of the research found that 1) the overall satisfaction of school administrators in Lopburi Primary Educational Service Area 1 based on the Tri-sikkh principle was at a high level. When considering each aspect, it was found that the aspect with the highest average value was the satisfaction with the need for social acceptance, followed by the satisfaction with physical needs, and the aspect with the lowest average value was the satisfaction with the need for security or safety. 2) A comparison of satisfaction with the administration of school administrators in Lopburi Primary Educational Service Area 1 according to the Tri-sikkh principle, classified by individuals, found that school size, gender, age, and work experience had different effects on overall satisfaction with the administration of school administrators.